2022
DOI: 10.3390/foods11172686
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Blood versus Blond Orange Consumption: A Cross-Cultural Study in Four Countries

Abstract: Understanding consumer perceptions and attitudes to specific fruit is key information for not only increasing fruit consumption, but also for marketing reasons. It may also give clues to breeders to set quality objectives. This study explores different aspects that help to explain blood vs. blond orange consumption: availability and consumption habit, satisfaction attributes, facilitators and consumption barriers, consumption contexts, expectations and purchase intention. The study was conducted in China, Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In recent years, several studies have evaluated the effect of different visual aspects, such as external colouration, gloss, skin dehydration or pulp colour (green/orange colour), on consumer expectations and their choice of traditional mandarins [6,26,31]. Most of these studies, which confirm the importance that consumers attach to fruit appearance, have been based on fruit images because their use allows responses to be obtained from more consumers and cross-cultural evaluations can be made [14,26]. Furthermore, editing images can be very useful for evaluating specific fruit appearance aspects [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, several studies have evaluated the effect of different visual aspects, such as external colouration, gloss, skin dehydration or pulp colour (green/orange colour), on consumer expectations and their choice of traditional mandarins [6,26,31]. Most of these studies, which confirm the importance that consumers attach to fruit appearance, have been based on fruit images because their use allows responses to be obtained from more consumers and cross-cultural evaluations can be made [14,26]. Furthermore, editing images can be very useful for evaluating specific fruit appearance aspects [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The first red mandarin breeding programme was established in Italy [13], where most blood oranges originate and have a long-standing tradition in markets. In fact, a recent study with data from four countries (Italy, Spain, China and Mexico) has revealed Italy as the country with the greatest consumption of blood oranges, where 76% of the study's participants stated being habitual consumers of this kind of orange [14].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Among the Sicilian blood orange types, the most popular is ‘Tarocco’ which comprises numerous cultivars, differing in intensity of red pigmentation and ripening season, fruit shape and size, tree vigor, and productivity [ 8 ]. In recent years, blood oranges have gained vast popularity, and their consumption as fresh fruit or juice has increased and is extending to new countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%